The Effect of Educaplay-assisted Online Assessment on Student Learning Motivation in Sanskrit Lectures in the Undergraduate Hindu Religious Education Study Program - Tristananda, Putu Wulandari (Cetta: Jurnal Ilmu Pendidikan, 2024)
The purpose of this study was to determine the effect of Educaplay-assisted online assessment on student learning motivation in Sanskrit lectures in the Hindu Religious Education Undergraduate Study Program. This research was a quasi-experiment research. The population of this study were all third-semester students of the Undergraduate Hindu Religious Education Study Program in the 2023/2024 academic year. The research design used was a Nonequivalent Control Group Design (Pretest-Posttest). Hypothesis testing was carried out using the 1-way Anacova test. The results showed that the average pretest and posttest scores of the Experiment class were 69.2174 and 79.8261, respectively. The average pretest and posttest scores of the control class were 67.3043 and 69.6522, respectively. Based on hypothesis testing, a significance value of 0.000 was obtained, which is smaller than 0.05 (0.000 < 0.05). This means that H0 is rejected. It can be concluded that there are differences in learning motivation between students who are given online assessments assisted by Educaplay and students who are not given the same assessment in Sanskrit lectures in the Hindu Religious Education Undergraduate Study Program.